2021
DOI: 10.1136/bcr-2021-243692
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Ct values in differentiating COVID-19 reinfection versus prolonged viral shedding in an immunocompromised patient

Abstract: We describe the case of a 26-year-old man who presented to an outside hospital with concerns of blurred vision. He subsequently tested positive for COVID-19 and his lab work suggested acute leukaemia. The patient was admitted to our hospital and completed a course of remdesivir. He eventually tested negative for COVID-19 before initiating chemotherapy. Two days after starting chemotherapy, he developed a neutropenic fever and tested positive for COVID-19. Through this case, we aim to bring attention to patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Other parameters could be useful for the identification reinfections, such as variation in symptoms and Ct-values between first and second infections. The latter was proposed by other studies showing a significant difference in Ct-values between paired samples ( Ringlander et al., 2021 ) and supporting its use as marker to differentiate reinfections from persistence ( Julian et al., 2021 ). Nevertheless, our results show no significant variation in either symptoms or Ct-values and cannot support their use as markers of reinfections, even because Ct-values depends on external factors such as the time elapsed since the onset of symptoms.…”
Section: Discussionmentioning
confidence: 54%
“…Other parameters could be useful for the identification reinfections, such as variation in symptoms and Ct-values between first and second infections. The latter was proposed by other studies showing a significant difference in Ct-values between paired samples ( Ringlander et al., 2021 ) and supporting its use as marker to differentiate reinfections from persistence ( Julian et al., 2021 ). Nevertheless, our results show no significant variation in either symptoms or Ct-values and cannot support their use as markers of reinfections, even because Ct-values depends on external factors such as the time elapsed since the onset of symptoms.…”
Section: Discussionmentioning
confidence: 54%
“…Mathematical models are considered important tools that can be used for better understanding the in-host dynamics of human viral co-infections under the impact of the immune response. Cases of HTLV-I and SARS-CoV-2 co-infection were recorded [6,[13][14][15]. A mathematical model for HTLV-I and SARS-CoV-2 co-infection was developed and analyzed [58].…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al [12] reported that 94.2% of individuals infected with COVID-19 were also co-infected with many other types of micro-organisms, such as viruses, bacteria, and fungi. Co-infections with HTLV-I and SARS-CoV-2 were reported [6,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%